NEW TAXONS OF BENTHIC DIATOM ALGAE OF THE TILIGUL ESTUARY (THE NORTH-WESTERN PART OF THE BLACK SEA COAST) - О. О. Ковтун (Mìkrobìologìâ ì Bìotehnologìâ, 2008)
181 species and taxons of the diatom algae were revealed in benthos of the Tiligul Estuary. 74 of them are represented for the reservoir for the first time and 25 for the first time for the estuaries of the north-western part of the Black Sea. Cocconeis scutellum var. tiligulicus Kovtun var. nov. and Fallacia gusliakovi Kovtun sp. nov. are described as new species for science. The original micrographs are presented.